Specificity of Antisera to Human Fibrinopeptide A Used in Clinical Fibrinopeptide A Assays - Nossel, Hymie L; Butler, Vincent P, Jr.; Wilner, George D; Canfield, Robert E; Harfenist, Elizabeth J (Thrombosis and Haemostasis, 1976)
Distinction between fibrinopeptide A (FPA) and larger polypeptides containing the FPA sequence is critical for the interpretation of clinical results with FPA immunoassay methods. Therefore, the immunochemical reactivity of 14 rabbit anti-FPA sera with six different FPA containing antigens was studied in detail. Antigens tested included: fibrinogen; fragment E of fibrinogen; the amino-terminal disulfide knot of fibrinogen; Aα 1 (Ala)-51 (Met); Aα l(Ala)-23(Arg); and, FPA. Synthetic partial sequences of FPA were also tested. The 14 FPA-specific antisera were divided into 3 distinct categories with: I, FPA immuno-reactivity of larger polypeptides containing FPA approximately 1/100 of FPA on a molar basis; II, FPA immunoreactivity of the larger polypeptides intermediate between I and III; and III, FPA immunoreactivity of the larger polypeptides approximately equal to that of FPA on a molar basis. The antigenic determinants of a category I antiserum (R 2) are included in Aα 7(Asp)-16(Arg) with Asp(7), Phe(8) and Arg(16) being essential. When attached to FPA, the sequence Gly(17)-Arg(23) decreases the immunoreactivity of FPA with category I antisera 100-fold.The practical consequence of these findings is that, when category III antisera are employed, both FPA and larger FPA-containing polypeptides are equally immunoreactive. Since thrombin treatment of the larger polypeptides does not alter their immunoreactivity, category III antisera cannot discriminate between FPA and the larger polypeptides. On the other hand, with category I antisera, although the immunoreactivity of FPA itself is unaltered by thrombin treatment, larger polypeptides [e.g., Aα l(Ala)-23(Arg)] show a 100-fold increase in immunoreactivity following thrombin treatment and thus can readily be identified and separately quantitated. It is concluded that antisera with the specificity of category I are essential for the specific and accurate measurement of FPA, and for its distinction from larger FPA-containing polypeptides, in clinical plasma samples.